Structure of E3 ligase E6AP with a proteasome-binding site provided by substrate receptor hRpn10 - Gwen R. Buel (Nature Portfolio, 2020)
Human ubiquitin E3 ligase E6AP contains a Zn-binding AZUL domain. Here the authors identify and name RAZUL, a domain in proteasome substrate receptor hRpn10 that binds AZUL, recruiting E6AP to proteasomes, and they present the NMR structure of the RAZUL:AZUL complex, which forms an intermolecular 4-helix bundle.